The Influence of Service Quality, Tariff, and Celebrity Endorsers on the Decision to Revisit at Bali Zoo - Krisna Dwipayana, I Gede; Suasana, I Gst. A. Kt. Gd. (Asian Journal of Management Analytics, 2024)
This study aims to analyze the influence of service quality, tariffs, and celebrity endorsers on the decision to revisit Bali Zoo. Using quantitative data collected from 120 respondents, the research evaluates how these factors impact visitors' decisions. The results indicate that all three factors—service quality, tariffs, and celebrity endorsers—have a positive and significant effect on the decision to visit Bali Zoo. The findings suggest that improving service quality, setting competitive tariffs, and utilizing celebrity endorsers in promotions can enhance the likelihood of visitors returning. The study provides actionable recommendations for Bali Zoo managers, including staff training, pricing adjustments, and strengthening promotional strategies, thereby contributing to a better understanding of consumer behavior and tourism decision-making.